CLINICAL AND ECONOMICAL ASSESSMENTS OF METOPROLOL TARTRATE/SUCCINATE USAGE IN PATIENTS WITH ISCHEMIC HEART DISEASE - M. V. Soura (Столичная издательская компания, 2016)
Clinical and clinicoeconomical studies review is presented as well as results of author's comparative cost analysis on metoprolol tartrate (Betaloc) and metoprolol succinate (Betaloc ZOK) usage in patients with ischemic heart disease. Efficacy of metoprolol therapy is proven in randomized clinical studies in patients with angina and myocardial infarction (MI). In angina patients metoprolol prevents cardiac attacks, MI, reduces nitroglycerine consumption, increases exercise tolerability, prolongs the exercise time before ST segment depression (succinate better than tartrate), decrease of angina intensity. In MI patients metoprolol therapy reduces mortality, sudden death, recurring MI and the rate of early post MI angina attacks. Nowadays metoprolol is the only β-blocker having indication on secondary MI prevention. Besides for the present metoprolol succinate is the only β-blocker with proven direct antisclerosis effect. According to Swedish clinicoeconomical study in patients after MI secondary prevention with metoprolol therapy saves the costs in comparison with placebo. American clinicoeconomical model of metoprolol and atenolol usage in all patients with MI could result in significant reduction in mortality and recurring MI rate, prolong the life and improve its quality, save financial resources. The cost of monthly treatment of angina patient with metoprolol tartrate (Betaloc) and metoprolol succinate (Betaloc ZOK) is 135 and 354 rubles, respectively. The price range of comparative β-blockers in ascending order is the following: atenolol (Atenolol Nicomed) → metoprolol tartrate (Betaloc) → metoprolol succinate (Betaloc ZOK) → bisoprolol (Concor) → nebivolol (Nebilet). In conclusion, metoprolol therapy is the one of mostly economically reasonable approach.